Effects of the Mongolian Medicine Eerdun Wurile on the Expression of Fas and FasL Post Retinal Ischemia‑Reperfusion Injury in Rat - Li, Changsheng; Chultumsuren, Yeruult; Bao, Manjie; Sukhee, Munkhbat; Byambajav, Tserenlkham; Damdinjav, Davaadagva (Trends in Immunotherapy, 2025)
The purpose of this study is to examine how the traditional Mongolian medicine Eerdun Wurile affects Fas and FasL proteins following retinal ischemia-reperfusion injury (RIR) in rats. We used healthy adult rats (n=68) dividing them randomly into 5 groups: a control (n=4), a model (n=16), and three Eerdun Wurile treatment groups (n=16 each): high, medium, and low–dose group. The RIR rat model was created using the high intraocular pressure method. Eerdun Wurile was administered via gavage twice daily for a week prior to modeling, while the model group received a medium dose of normal saline. We utilized hematoxylin and eosin (HE) staining to observe retinal morphological changes under an optical microscope. Additionally, we employed immunohistochemical staining to determine how the treatment affected protein expression in the retinas of RIR rats. We observed that 24 hours after RIR, the retinal layers exhibited significant edema, disorganized structure, nuclear atrophy, and a substantial infiltration of inflammatory cells in the ganglion cell layer, accompanied by a reduction in ganglion cell count. As time progressed to 48 and 72 hours post-RIR, the retinal swelling gradually diminished, the retina became thinner, and numerous cells displayed vacuolation and nuclear condensation. Our findings suggest that Eerdun Wurile mitigates retinal cell damage caused by ischemia-reperfusion in rats by suppressing the expression of Fas and FasL proteins in rat retinal cells following RIR induction. Notably, the high-dose Eerdun Wurile group demonstrated significantly greater efficacy compared to the medium- and low-dose groups.